Cytological diagnosis in a clinically unsuspected case of disseminated BCGosis: A case report. Issue 4 (19th December 2019) - Mittal, Medha; Mahajan, Nidhi; Khatri, Arti; Rai, Anuradha; Saigal, Karnika
Abstract: Bacille Calmette‐Guerin (BCG) vaccine is administered worldwide to neonates and considered safe. Serious complications like disseminated BCGosis are extremely rare occurrences (<1 per million vaccinations). A 6 months male was brought to paediatric outpatient department with fever and swelling over the dorsum of the left hand for 5 days. On examination, he was febrile and had hepatosplenomegaly. X‐ray of the hand showed lytic lesions in the first and second metacarpals. Provisional clinical diagnosis included Langerhans cell histiocytosis, congenital syphilis, and haematological malignancy. Fine Needle Aspiration Cytology (FNAC) was done from the swelling and showed diffuse sheets of histiocytes with both intracellular and extracellular rod‐shaped unstained structures along with inflammatory cells. These ghost images stained positive with ZN stain. A cytological diagnosis of atypical mycobacteria vs leprosy was made. Child was revisited and found to have an active BCG scar. Further investigations showed low serum IgM and positive AFB culture. These bacilli were confirmed by GenoType MTBDR plus test as Mycobacterium bovis. Despite Antitubercular therapy, the patient succumbed to death. This case highlights the variable clinical presentation of BCGosis. Its occurrence may unmask any underlying immunodeficiency. If unfamiliar with the above cytological features and in absence of routinely performed special stains, the cytopathologist may miss these notorious organisms and treat such cases like suppurative lesions. To conclude, an early and definitive diagnosis of BCGosis can be established on FNAC which would ensure timely management and better outcome in this highly lethal entity.